FINITE GROUPS WITH THEIR AUTOMORPHISM GROUPS HAVING ORDERS \(4pq ^2\) (2 < p < q) - Zeng, Yu; Chen, Guiyun (Italian Journal of Pure and Applied Mathematics, 2013)
The authors find all finite nilpotent groups with automorphism groups having orders 4pq2 and prove that there exists no finite non-nilpotent group such that |Aut(G)| = 4pq2 (2 < p < q, p ∤ q2 - 1). So, the authors classify finite groups with their automorphism groups having orders 4pq2 (2 < p < q, p ∤ q2 - 1).